Oculomotor nerve palsy following coronary artery bypass graft surgery: can pituitary apoplexy complicate the post-operative course of cardiac surgery?. Issue 7 (31st July 2021) - Alkhaibary, Ali; Alsubaie, Noura; Alharbi, Ahoud; Alghanim, Noor; Khairy, Sami; Almuntashri, Makki; Alwohaibi, Mohammed; Alarifi, Abdulaziz; Aloraidi, Ahmed; Alkhani, Ahmed
Abstract: Oculomotor nerve palsy, due to pituitary apoplexy, has been previously reported in the literature. However, the association with coronary artery bypass graft surgery (CABG) is rarely investigated. This article reports a case of pituitary apoplexy presenting with oculomotor nerve palsy following CABG. A 65-year-old male, known to have ischemic heart disease, diabetes mellitus and hypertension, presented with ptosis, diplopia and anisocoria that developed after 1 day of CABG. Radiological imaging demonstrated a pituitary adenoma with acute/subacute hemorrhage causing mild mass effect on the cavernous sinus. Considering the acute state of bypass surgery and pre-existing cardiac co-morbidities, expectant management was considered. The visual acuity and palsy gradually improved. Pituitary apoplexy, following CABG, is a rare phenomenon in the post-operative period. High index of suspicious is required to promptly identify high-risk patients to avoid further neurological sequelae.